2019
DOI: 10.4012/dmj.2017-247
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the physical properties and color stability of aesthetic restorative materials caused by various beverages

Abstract: This study investigates the effects of various beverages on the wettability, microhardness, and color stability of aesthetic dental restorative materials. A contact angle analyzer, Vickers hardness tester, and spectrophotometer were used to characterize the properties of the materials and a total of 225 specimens were prepared: 75 each for a resin composite, compomer, and giomer. Ingestion of energy drinks and cola caused the greatest deterioration in wettability and microhardness, and coffee caused the most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 20 publications
6
42
0
7
Order By: Relevance
“…Regarding microhardness, the use of the Vickers microhardness technique was predominant in the in vitro studies observed, due to its accuracy for the methodologies used (Garoushi, Vallittu, Lassila, 2018;Parasher et al, 2020;Spajic et al, 2019 Research, Society and Development, v. 10, n. 3, e43310313413, 2021(CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i3.13413 Fleming, 2015Tanthauch et al, 2014). Instead to what was observed for flexural properties, in some studies the material suffered a reduction in microhardness when submerged in some solutions (Choi et al, 2019;Silva et al, 2019;Tanthanuch et al, 2014;Kooi et al, 2012). In addition, the polymerization protocol influenced the microhardness of the giomer, as well as the supervised whitening at home protocol (Kaya et al, 2018;Kimyai et al, 2017;Gonulol, Ozer, Tunc, 2016).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding microhardness, the use of the Vickers microhardness technique was predominant in the in vitro studies observed, due to its accuracy for the methodologies used (Garoushi, Vallittu, Lassila, 2018;Parasher et al, 2020;Spajic et al, 2019 Research, Society and Development, v. 10, n. 3, e43310313413, 2021(CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i3.13413 Fleming, 2015Tanthauch et al, 2014). Instead to what was observed for flexural properties, in some studies the material suffered a reduction in microhardness when submerged in some solutions (Choi et al, 2019;Silva et al, 2019;Tanthanuch et al, 2014;Kooi et al, 2012). In addition, the polymerization protocol influenced the microhardness of the giomer, as well as the supervised whitening at home protocol (Kaya et al, 2018;Kimyai et al, 2017;Gonulol, Ozer, Tunc, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Extremely relevant information was verified in the studies by Choi et al (2019) and Tanthanuch et al (2014) who observed that the submersion of the giomer in Cola-based soft drink brought a significant rate of reduction in the hardness of the material. In addition, the study by Silva et al (2019) achieved significant reduction in the microhardness of the material with its immersion in coffee associated with the brushing simulation, as well as with its immersion in artificial saliva, showing that the Knoop microhardness of the giomer was inferior to that observed by the nanoparticulate composite.…”
Section: Microhardnessmentioning
confidence: 87%
“…8 Some drinks in the diet of the population have greater potential to change the color of composite resins, such as coffee, tea, juices and wine. 9,10 Coffee is a commonly consumed beverage and has strong potential to stain both dental structure and resin materials, because it has water-soluble dyes and polyphenols, such as tannin, caffeine and caffeic acid. Lower polarity causes the coffee pigments to have higher adsorption and dye penetration in the composite resin.…”
Section: Introductionmentioning
confidence: 99%
“…However, although manufacturers improve the composition of composite resins, the chemical environment is still an aspect with appreciable influence on the degradation of this material [2]. The hydrophilic characteristics of the resin matrix influence the degree of water sorption and, therefore, acidic drinks can impair the surface integrity of the composite resins, aesthetically and physically, tending to cause erosion on the surface of material, and this degradation is related to the content and distribution of inorganic fillers [2,3]. Energy drinks are widely consumed, mainly by athletes, to promote well-being and better physical performance, due to the presence of components such as coffee, taurine and glucuronolactone [4][5][6].…”
Section: Introductionmentioning
confidence: 99%